The Effectiveness of Online Learning in Pre-University Education During the Pandemic - The Case of Albania - Halilaj, Alfred (European Journal of Multidisciplinary Studies, 2022)
Online learning was a challenge for education in general. The covid-19 pandemic forced the general closure of the population and made it difficult for learning to take place. Some developed countries had more opportunities and experience to practice online learning. Many other countries, particularly developing countries, encountered extraordinary difficulties during this process. The lack of experience, digital infrastructure and investments in online learning face the Albanian education system with many problems. During the pandemic, there was a commitment of teachers to overcome these problems, but the results were low. In order to understand what was the level of online learning in Albania, we will present, through data collected from online questionnaires, the degree of effectiveness. Using direct interviews with students, teachers and parents we will explain the difficulties encountered as well as their reflections on this way of learning. We will also compare the official documents with the data extracted from the study to bring some recommendations that will help in the development of this way of teaching in the future. The analysis of the collected data will be developed in a narrative way to elaborate the most complete understanding of the reality of online learning in Albania during the pandemic.
Keywords: Education, online learning, covid-19 pandemic, education system, Albania